A contribuição das parcelas do rendimento domiciliar para a desigualdade de renda nos espaços rurais do Nordeste - Rocha, Helder Pita (2009)
Income inequality in Brazil declined in recent years. Doubts, however, weaken the universalization of this fall in regions or specific areas, especially where there are high rates of illiteracy, a significant portion of the population is poor and / or job opportunities are scarce especially for labor unskilled and the consequent weak economic development, enabling environment for the maldistribution of income. This research aims to show the evolution of inequality in the distribution of household income per capita, measured by the Gini index and to detect what were the shares of household income contributed to inequality, and to determine the percentage contribution of the components of household income. Was used as a methodology to decompose the Gini index of income sources. The database used as a source the National Household Sample Survey (PNAD), the period from 1997 to 2007. The rural areas of the Northeast not metropolitan, the State of Ceará and the Metropolitan Region of Fortaleza were the areas of this research, since they fit in this context. The results showed that income inequality has fallen, not permanently, in the Northeast. In the other two areas studied, it varied throughout the period without many changes. The plots and Other Works, Retirement and Pensions officials reinforced the inequality in three geographical areas and social programs to transfer income to the poorest countries have had significant participation in the continual reduction of the Gini index, especially in the rural Northeast.